2021
DOI: 10.1007/s40615-021-00992-y
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination and Stress Among Asian Refugee Populations During the COVID-19 Pandemic: Evidence from Bhutanese and Burmese Refugees in the USA

Abstract: Objectives To measure COVID-19 pandemic-related discrimination and stress among Bhutanese and Burmese refugees in the USA and to identify characteristics associated with these two measures. Methods From 5/15–6/1/2020, Bhutanese and Burmese refugee community leaders were invited to complete an anonymous, online survey and shared the link with other community members who were English-proficient, ≥18 years old, and currently living in the USA. We identified characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 36 publications
(49 reference statements)
2
20
0
Order By: Relevance
“…Further, using two separate typologies for racial microaggression (behavioral aggression and verbal aggression) and discrimination (workplace discrimination and institutional racism), I found that South Asian Americans experienced the most racial discrimination (e.g., verbal aggression, workplace discrimination, and institutional racism) across three Asian American ethnic groups, though the Southeast Asia group experienced the most behavioral aggression. The multivariate findings support prior studies [9,10,[18][19][20][21] showing that increased racial discrimination was associated with worse health status among Asian populations in America. For NAAS respondents, increased workplace discrimination and institutional racism yielded decreased odds of reporting good health status.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Further, using two separate typologies for racial microaggression (behavioral aggression and verbal aggression) and discrimination (workplace discrimination and institutional racism), I found that South Asian Americans experienced the most racial discrimination (e.g., verbal aggression, workplace discrimination, and institutional racism) across three Asian American ethnic groups, though the Southeast Asia group experienced the most behavioral aggression. The multivariate findings support prior studies [9,10,[18][19][20][21] showing that increased racial discrimination was associated with worse health status among Asian populations in America. For NAAS respondents, increased workplace discrimination and institutional racism yielded decreased odds of reporting good health status.…”
Section: Discussionsupporting
confidence: 87%
“…Asians and Asian Americans, regardless of their connection to China, have been blamed for the pandemic [21,40,41]. As a mechanism of aggression, discrimination, and even hate crimes, this racialized condemnation may have far-reaching effects on Asian populations [40], including worsening health conditions [21,41]. This study may also provide implications to assess the impacts of the COVID-19 pandemic on wellness of Asian American populations.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Poverty, language barriers, and multigenerational living situations likely exacerbate the risk. One study evaluating refugees from Bhutan and Myanmar, representing 14% and 21% (respectively) of resettled refugee communities in the United States used questionnaires to determine COVID-19 incidence in essential and nonessential workers 12 . Not surprisingly, essential workers had higher self-reported infection, which may be underestimated given the nature of the survey.…”
Section: Introductionmentioning
confidence: 99%